Screening of bacterial isolates as potential biocontrol agents against Botrytis cinerea in causing gray mold disease of tomato (Solanum lycopersicum L.) - Ali, Arafat Hashim (2018)
Gray mold disease, caused by the fungus Botrytis cinerea, is the most significant disease affecting tomato cultivation causing serious yield losses. In order to reduce the usage of synthetic pesticides in farm, an alternative control disease method is necessary for sustainable disease control. Biocontrol agents have been known to produce effective antimicrobial compounds to control phytopathogens. So that, this study was carried out (i) to isolate and screening bacteria against B. cinerea, (ii) to identify the most potential bacteria, determine the antimicrobial compounds produced by selected bacteria isolates and evaluate the efficacy of selected bacteria isolates against B. cinerea in vivo. A total of 43 bacterial isolates were obtained from tomato fruit. All the isolates were tested against B. cinerea by dual culture test on PDA and 12 isolates showed growth inhibition against B. cinerea. The best five isolates with more than 65% inhibition of radial growth (PIRG) were selected for the subsequent experiments. Findings in dual culture assay revealed that BM11 and BC4 were the most effective isolates, which have the PIRG of 82.5% and 71.8%, respectively. BM11 and BC4 isolates were then subjected to molecular identification using 16S rDNA gene region. The results revealed that BM11 and BC4 isolates were Pseudomonas protegens and Brevibacterium casei, respectively. Bioactive of volatile compounds from ethyl acetate crude extract were identified using gas chromatography-mass spectrometry (GCMS). Ten major bioactive compounds were successfully identified from both bacteria isolates and that possibly were responsible for the antifungal activity in this study. The minimum inhibitory concentration (MIC) showed that there were significantly differences (P ≤ 0.05) against B. cinerea at different concentrations tested. In vivo study showed that the efficacy of the ethyl acetate crude extract of P. protegens and B. casei against B. cinerea by suppressing disease lesion on treated tomato fruit at 0.86 cm and 1.03 cm, respectively at 30 days after inoculation as compared to positive control (5.47 cm) at the same assessment period. These findings suggested that the extract manage to suppress fungal disease development effectively. Based on overall findings suggested that P. protegens and B. casei were the most promising biological control agent in controlling gray mold disease in tomato fruit.